2023
DOI: 10.1002/cyto.b.22113
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric assessment for minimal/measurable residual disease in B lymphoblastic leukemia/lymphoma in the era of immunotherapy

Abstract: Minimal/measurable residual disease (MRD) is the most important independent prognostic factor for patients with B‐lymphoblastic leukemia (B‐LL). MRD post therapy has been incorporated into risk stratification and clinical management, resulting in substantially improved outcomes in pediatric and adult patients. Currently, MRD in B‐ALL is most commonly assessed by multiparametric flow cytometry and molecular (polymerase chain reaction or high‐throughput sequencing based) methods. The detection of MRD by flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 133 publications
0
10
0
Order By: Relevance
“…The analysis strategy of an MFC‐BMRD approach completely depends on gating the target cells for focused and deeper subsequent analysis. CD19 has been traditionally used for this purpose due to its consistent expression throughout most parts of the B cell maturation 11,13,40 . Recently, CD19‐directed therapies, including blinatumomab and anti‐CD19‐CAR‐T, have improved the outcomes of relapsed/refractory B‐ALL 43–45 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis strategy of an MFC‐BMRD approach completely depends on gating the target cells for focused and deeper subsequent analysis. CD19 has been traditionally used for this purpose due to its consistent expression throughout most parts of the B cell maturation 11,13,40 . Recently, CD19‐directed therapies, including blinatumomab and anti‐CD19‐CAR‐T, have improved the outcomes of relapsed/refractory B‐ALL 43–45 .…”
Section: Discussionmentioning
confidence: 99%
“…We designed a 15‐color BMRD assay incorporating markers based on our previous experiences and published literature review 2,13,28,39,40 . Details of the antibody panel are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, use of these therapies pose great challenges for clinical cytometry labs in the assessment of post-treatment samples, especially in the detection of measurable/ minimal residual disease (MRD). In this issue, Chen, Gao, et al (2023) provided an overview of MRD detection in B-lymphoblastic leukemia/ lymphoma in the era of immunotherapy, and Gao et al (2023) focused their review on the impact of targeted therapy on mature B-and plasma cell neoplasms utilizing flow cytometry assessments. In both reviews, the authors illustrated the challenges, identified the problems, and provided a list of available options and solutions.…”
mentioning
confidence: 99%
“…Targeted immunotherapy demonstrated encouraging results in recent years but induces significant changes in the phenotype of leukemic blasts concurrently. Therefore, alternative gating strategies have gained importance and potential CD19 substitutes have been proposed (Chen et al, 2023; Mikhailova et al, 2022).…”
mentioning
confidence: 99%